On the equation A∇u+∇utA=G. (July 2020) - Bandyopadhyay, S.; Dacorogna, B.; Strütt, D.
Abstract: Let Ω ⊂ R n be an open set, A ∈ R n × n and G : Ω → R n × n be given. We look for a solution u : Ω → R n of the equation A ∇ u + ∇ u t A = G . We also study the associated Dirichlet problem.